Causing The Lecturers to Use Diagnostic Assessment to Find Out The Weaknesses of Students in Understanding Basic Reading in The Third Semester Students of Universitas Nahdlatul Ulama Blitar - Bagus Waluyo; Oikurema Purwati; Slamet Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2020)
This research is based on the still problematic confusion of basic reading lecturers to determine the weakness of students in understanding basic reading so that there are still a number of students who are completely weak in the analysis of discourse content and have not been detected clearly. Diagnostic assessment to find out the weaknesses of students in understanding basic reading in the third semester students of of Universitas Nahdlatul Ulama Blitar is applied in this study. The research method used is a descriptive qualitative method. data collection technique in this study is using interview technique. In this study, the source of the data is the third semester Basic Reading Lecturer at Universitas Nahdlatul Ulama Blitar. The results show that the strong desire of the third semester basic reading lecturers at Universitas Nahdlatul Ulama Blitar to use Diagnostic assessment resulted from several factors, namely: a) easy to understand student's ability in reading analysis, and b) easy factor to know the weaknesses of students in understanding reading. From the description above it can be concluded that Diagnostic assessment is an appropriate facility for lecturers to find out the weaknesses of students who are the top priority in learning outcomes.